A formação de professores para o ensino de ciências da natureza e matemática em escolas do campo : reflexões críticas a partir da experiência do Curso de Licenciatura em Educação do Campo da UFMA - Diniz, Diana Costa (2021)
This paper investigates teacher formation from the Degree Course in Rural Education, Natural Sciences and Mathematics at UFMA. It sought to understand how the formation of teachers in the area of Natural Sciences and Mathematics, in the Degree Course in Rural Education at UFMA is dialoguing with the principles constructed by Rural Education in terms of the conception of science, knowledge and nature. The main goal was to analyze the formation of educators in Natural Sciences and Mathematics in the Rural Education, Degree Course, identifying in its curriculum if the concepts of science, knowledge and nature are aligned with those that the Rural Education movement built. Other questions emerged from the guiding problem: What are the constitutive elements of the formation of teachers of basic rural education in the degree courses, considering the conception of science, knowledge and nature? What conceptions of science, knowledge and nature underlie the curriculum of the teacher’s formation on Rural Education in the area of Natural Sciences and Mathematics at UFMA? How does the formation of educators materialize in the Degree Course in Field Education in Nature and Mathematics Sciences at UFMA? For that, we outlined the following specific objectives: 1) Identify in the documents and regulations, as well as the historical context, the conceptions of teacher training for basic education in the context of Brazilian education; 2) Discuss the conception of science, knowledge and nature that defines the curriculum for the formation of Rural Education teachers in the area of Natural Sciences and Mathematics; 3) Reflect on the formation of educators in Natural Sciences and Mathematics and its materialization in the formative process of the Degree Course in Rural Education at UFMA. The theoreticalmethodological conception that supported our studies was the historical-dialectical materialism. The research was based on assumptions of a qualitative nature, with the following data collection instruments: documental analysis of the course's political-pedagogical project, course plans for disciplines and legislation; bibliographic research and field research with semistructured interviews with ten professors and ten students. From the collected data, the following analysis categories emerged: Pedagogy of the Alternating Cycle, Research, Interdisciplinarity and Educational Praxis. As a reference for analysis, content analysis was employed, structured in the following units of analysis: the curricular organization of the course, the projects to encourage teaching and research, the internship, the contents and methodologies developed by the teachers. The results achieved showed that the work carried out in this experience, despite suffering the determinations of the hegemonic conception of training centered on the teaching of watertight contents and on isolated teaching work in classrooms disconnected from life, has pointed to possibilities of changing the way people deal with knowledge. and with the organization of the pedagogical work. It allows us to identify the necessary alteration of the formative matrix guided by a conception of science, knowledge and nature as praxis aiming at overcoming the fragmentation of contents.